2017
DOI: 10.7717/peerj.4044
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic and population insights of the Asian common toad (Bufo gargarizans) in Korea and China: population isolation and expansions as response to the ice ages

Abstract: The effects of ice ages on speciation have been well documented for many European and North American taxa. In contrast, very few studies have addressed the consequences of such environmental and topographical changes in North East Asian species. More precisely, the Korean Peninsula offers a unique model to assess patterns and processes of speciation as it hosts the northern- and eastern-most distribution limit of some widespread Asian taxa. Despite this, studies addressing phylogeographic patterns and populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 93 publications
8
56
0
Order By: Relevance
“…; [40]). The same pattern is expected for species distributed across the Yellow sea, such as Bufo gargarizans [41] and Pelophylax nigromaculatus [42]. Other species are expected to have seen their range split during past fluctuations of the sea level, such as Pelophylax chosenicus and P. plancyi [43], and Dryophytes suweonensis and D. immaculatus [44][45][46][47], the focal species of this study.…”
Section: Introductionsupporting
confidence: 63%
“…; [40]). The same pattern is expected for species distributed across the Yellow sea, such as Bufo gargarizans [41] and Pelophylax nigromaculatus [42]. Other species are expected to have seen their range split during past fluctuations of the sea level, such as Pelophylax chosenicus and P. plancyi [43], and Dryophytes suweonensis and D. immaculatus [44][45][46][47], the focal species of this study.…”
Section: Introductionsupporting
confidence: 63%
“…Both natural and artificial dispersals could have contributed to this pattern. Natural dispersal could have been facilitated by land connections among the countries during prehistoric glacial periods via three potential routes (via the Ryukyu Islands, around the Yellow Sea or rafting across the East China Sea, Kim et al 2007;Borzee et al 2017;Park et al 2017). Artificial dispersal could have been facilitated by the human shipping connections between cities in the Shandong Peninsula and east coasts of China and cities in Japan and Korea (Fogel 2000;Mitsuhashi et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Such value as a biodiversity reservoir seems to be directly related to the role of the BDDG as a Pleistocene refugium, as shown by recent phylogeographic and palaeoecological studies (plant species reviewed in Chung et al, 2017 ; for animals see Borzée et al, 2017 ; Lee et al, 2018 ). Chung et al ( 2017 ) critically reviewed the literature on genetic diversity and phylogeography of plants for which Korean populations were studied and found clear signals of the role of these mountains as a glacial refugium: [1] Korean populations showed higher intrapopulation genetic diversity than populations located further north (and, in some cases, with latitudinal decreases of genetic variation; i.e., consistent with the “southern richness” vs. “northern purity” paradigm of Quaternary biogeography; Hewitt, 2000 ; Hu et al, 2009 ); [2] Korean populations harbored ancestral haplotypes; and [3] Korean populations exhibited significant amounts of unique haplotypes/alleles (Chung et al, 2017 ).…”
mentioning
confidence: 88%
“…Kim et al ( 2013 ) detected eight mitochondrial cytochrome b haplotypes from Korean populations (including some from the BDDG) of the raccoon dog Nyctereutes procyonoides , but only five from the Russian Far East. Borzée et al ( 2017 ) found more mitochondrial haplotypes from populations of the Asian common toad ( Bufo gargarizans ) in the BDDG and its vicinity compared to other lowland localities (mean number of haplotypes; 3.33 vs. 2.43). Similarly, Jo et al ( 2017 ), using five microsatellite loci, found that populations of the striped field mouse (Apodemus agrarius) on the BDDG and its vicinity harbor significantly higher levels of within-population genetic diversity than those from lower habitats (by excluding a population on Jeju Island; H e = 0.864 vs. 0.805, P = 0.017, Mann-Whitney U test).…”
mentioning
confidence: 99%